Mentalizing the therapist – Therapist experiences with short-term mentalization-based therapy for borderline personality disorder: A qualitative study - Søndergaard, Amanda Ark; Juul, Sophie; Poulsen, Stig; Simonsen, Sebastian (Frontiers in Psychiatry, 2023)
Background Mentalization-Based Therapy (MBT) was originally developed as a structured psychotherapy approach developed to treat borderline personality disorder (BPD) lasting up to 18 months in outpatient settings. However, a short-term (5 months) MBT program has recently been developed. No studies have investigated how MBT therapists experience the shift towards conducting short-term MBT for BPD. Objective The objective of this study was to explore therapist experiences with conducting short-term MBT for outpatients with BPD in the Danish mental health services. Methods Semi-structured qualitative interviews were conducted with seven therapists about their experiences with short-term MBT after a one-year pilot phase. The interviews were verbatim transcribed and analyzed using thematic analysis. Results The following four major themes from the therapists’ experiences with short-term MBT were found in the qualitative analysis: (1) The longer the better, (2) Change processes can be intellectual or experiential, (3) Short-term therapy is hard work, and (4) Termination is more challenging in short-term MBT. Conclusion Most therapists were overall reluctant towards changing from long-term to short-term MBT. These therapist experiences could inform implementation of short-term MBT in mental health settings in the future.